Kinetic patterns of vacuum distillate catalytic cracking on different catalyst - Nazarova G. Yu. Galina Yurievna; Ivashkina E. N. Elena Nikolaevna; Ivanchina E. D. Emilia Dmitrievna; Burumbaeva G. R. Galiya Rashidovna; Kaliev T. A. Toleubek Arystanbekovich; Seytenova G. Zh. Gayni Zhumagalievna (2021, 2021)
Title screen